A pilot randomized trial of nebulized amphotericin in patients with allergic bronchopulmonary aspergillosis - Ram, Babu; Aggarwal, Ashutosh N; Dhooria, Sahajal; Sehgal, Inderpaul Singh; Garg, Mandeep; Behera, Digambar; Chakrabarti, Arunaloke; Agarwal, Ritesh (The Journal of asthma, 2016)
Nebulized amphotericin B (NAB) has been used in the management of acute stage and exacerbations of allergic bronchopulmonary aspergillosis (ABPA). Whether NAB can prevent exacerbations of ABPA is not known. Herein, we evaluate the efficacy and safety of NAB in subjects with ABPA complicating asthma. Consecutive subjects of ABPA with recurrent exacerbations were randomized to receive either NAB plus nebulized budesonide (NEB) or NEB alone. The primary outcome was the time-to-first exacerbation of ABPA. The secondary outcomes were the number of subjects with ABPA exacerbations, ACQ7 scores, lung function, IgE levels, and adverse effects of treatment. Twenty-one subjects (14 men; mean age, 32.3 years) were randomized to either the NAB (n = 12) or the NEB (n = 9) arm. The baseline characteristics were similar in the two groups. The time-to-first exacerbation was similar in the two groups. At one year, the numbers of patients experiencing exacerbation was significantly lower in the NAB arm (1/12 [8.3%] vs. 6/9 [66.7%]; p = 0.016). The other secondary end points were not different between the two groups. There were no major adverse events leading to discontinuation of any of the study drugs. Three patients experienced bronchospasm after first dose of NAB; however, the subsequent doses were well tolerated. NAB seems to be beneficial in decreasing the frequency of exacerbations in patients with ABPA complicating asthma. Larger trials are required to confirm our study results.